The Role of Narcissism and Should Counterfactual Thinking in the Hindsight Bias - KAUSEL, Edgar E. (Institutional Knowledge at Singapore Management University, 2013)
The current study examined the effects of narcissism and should counterfactual thinking on the hindsight bias, and the moderating role of outcome favorability. Experimental data from 169 participants revealed that narcissism and outcome favorability interactively influenced should counterfactual thinking, which in turn influenced the hindsight bias.